Symptoms of PTSD Among Adolescents in Malaysia 4 Years Following the 2004 Tsunami - Siti Raudzah, Ghazali; Ask, Elklit; Khatijah, Yaman; Mariah, Ahmad (Taylor & Francis, 2013)
While physical infrastructure is quickly rebuilt following a natural disaster, the psychological effects on victims are often neglected. This study investigated symptoms of posttraumatic stress disorder (PTSD) among adolescents who were exposed to the 2004 tsunami in Northern Peninsular Malaysia. The randomly selected participants were 216 adolescents living in small villages affected by tsunami ranging in age from 13 to 19 years. Males constituted 47.7% (103) and the remaining were female. This study was a cross-sectional research design in which PTSD symptoms were assessed by The Child Posttraumatic Stress Reaction Index (CPTS-RI). Results showed that 8.3% reported having severe symptoms of PTSD, 39.8% having moderate symptoms, 42.1% having mild symptoms, and 9.7% reported having no significant symptoms of PTSD. Females reported significantly higher on criterion B symptom score than male participants. Results of multiple regression analysis indicated that number of lifetime traumas and age were significant predictors for PTSD score. The prevalence of PTSD symptoms was still high even four years after the tsunami. This finding was consistent with previous studies. Further discussion on the research findings and several recommendations are put forward.